2011
DOI: 10.1080/10410236.2011.566831
|View full text |Cite
|
Sign up to set email alerts
|

“Can You Spare an Organ?”: Exploring Hispanic Americans' Willingness to Discuss Living Organ Donation With Loved Ones

Abstract: Living organ donation offers a means of overcoming the shortage of viable organs available for transplant: a shortage particularly problematic among Hispanics. One barrier standing between those in need of a kidney and a successful transplant operation is an inability, and often lack of desire, to talk to loved ones about the need for a living donation. With an eye on future intervention approaches, and guided in part by the theory of planned behavior, this research effort sought to explore the factors associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…As patients with ESRD commonly avoid accepting donor offers to protect donor wellbeing or asking others to donate, 13,19,21,[70][71][72] patients may find it helpful to refer their family members to Infórmate to raise awareness of LKD as a treatment option and inform them about the process of becoming a donor. UCD participants had higher posttest knowledge gains than did NMH participants, most likely because website content was closely aligned to NMH's HKTP curriculum.…”
Section: Discussionmentioning
confidence: 98%
“…As patients with ESRD commonly avoid accepting donor offers to protect donor wellbeing or asking others to donate, 13,19,21,[70][71][72] patients may find it helpful to refer their family members to Infórmate to raise awareness of LKD as a treatment option and inform them about the process of becoming a donor. UCD participants had higher posttest knowledge gains than did NMH participants, most likely because website content was closely aligned to NMH's HKTP curriculum.…”
Section: Discussionmentioning
confidence: 98%
“…The HKTP has found that asking patients to bring "living donors" can reduce their willingness to participate and result in patients not asking their family to donate, which has been observed elsewhere. 17,19,30 Further, Hispanic family members often do not realize their potential eligibility to donate, given a lack of knowledge and cultural concerns about LKD and transplantation. Thus, the HKTP, by inviting family members in the education sessions, aims to enhance knowledge about transplantation and donation throughout the family, which increases family members' consideration of becoming a living donor, and plays an important role in moving along treatment decisions because Hispanic family elders (e.g., the grandmother) often influence and guide these decisions.…”
Section: Hktp's Core Featuresmentioning
confidence: 97%
“…Including the patient's family in education sessions can facilitate communication about LDKT within the family and with providers. 30 To our knowledge, no previous studies have assessed the effectiveness of culturally competent transplant centerbased interventions to increase Hispanic LDKT rates. Although many centers provide materials in Spanish, 31 there are no published accounts of other comprehensive transplant programs that are tailored to address Hispanics' cultural concerns.…”
mentioning
confidence: 99%
“…To date, the effect of race/ethnicity on LDKT access has not been adequately described by the kidney transplant community, particularly in capturing differences in barriers within widely diverse racial/ethnic groups or in identifying differences in point-of-access problems. However, broadly described and starting with influence of cultural identity, some minorities with kidney failure may cope with the need for transplantation and the possibility of LDKT differently than non-Hispanic whites, and they may be more likely to deny the need for kidney transplantation, have religious objections to transplantation, question the survival and quality of life benefits of transplantation, and mistrust the healthcare system because of their experience of discrimination in accessing healthcare in the past (14,(26)(27)(28)(29)(30). Even for blacks and Hispanics who have decided to pursue transplantation and are on the waiting list, many have not actively considered the LDKT option and some harbor distrust and equity concerns affecting willingness to participate in KPD (29,31,32).…”
Section: Race/ethnicitymentioning
confidence: 99%